PARTISIPASI PEMASOK DALAM PENYELENGGARAAN E-PROCUREMENT DI KOTA JAMBI - Johannes -; Ade Titinifita; Novitasari - (DIGEST MARKETING, 2012)
This research aims is to explain supplier participation on e-procurement practice in Jambi City. Conceptualy e-procurement called as LPSE, where also identically with SPSE terminology. According to theoritical point of view, the implementation of e-procurement is more efficeient than conventional auction.  The success of e-procurement implementation however is mainly determined by supplier participation. Survey is conducted to the supliers in the city of Jambi where the respondents is small business that followed e-procurement practice. Research resulst shows that e-procurement practice is not optimally followed by the suppliers. There was an indication that supplier incompetence in technology caused the supplier less participate. It is worried to be the problems for LPSE not funtioned optimally on the economy in the future. Base on the primary data processing,  it is found that the supplers participation model is  Y = -0,027 – 0,011X1 + 0,223X2 + 2,289X3 + 0,958X4 + 2,404X5 where the value for independent variable  is  X1 (0,991), X2 (0,824), X3 (0,026), X4 (0,342), dan X5 (0,019) respectively. The statistical results also found that the value of R (coefficient determination) is 34 percent where the Pvalue is 0.000 percent. Hence it is known that model can explain the variation of supplier participation as  much as  34 persent, where varibles that affects significant partially are X3 and X5 (supplier perception on LPSE reliability and supplier network). Research conclusion here is the supplier participation in e-procurument practice could be explained by the five variabels, they are: perception on the fairness, complain responsiveness, timely respon internal supplier efficiencies, and suppliers networking. Furthermore, in order to maximize the roole of LPSE to increase the efficiencies and smalholder competitiveness, the role of local government is needed.  Efficiency could be establised caused by some activities, mainly the suplier process activities. If the activities connect the supplier each other they are not only learn, but increase the efficiency. Local government that has autority to diversify LPSE service, actually could monitor service attribute that needed by the supplier. Service that offering by the local government should implement innovation to make all service attribute to be meaningful for the supplier.  The higher the importance of supplier to the service attribute, the more they participate on e-procurement.